In Vitro Antioxidant And Antitumor Activity Of Polysaccharide Isolated From Ulva Fasciata - SHONIMA GOVINDAN M,; JIJI THOMAS,; G MURALEEDHARA KURUP, (International Journal of Pharma and Bio Sciences, 2012)
A water soluble polysaccharide was extracted from the edible green algae Ulva fasciata and isolated by Gel filtration chromatography. The antioxidant activity of the purified polysaccharide fraction was evaluated in vitro by superoxide radical scavenging assay, lipid peroxidation inhibition assay, hydroxyl radical scavenging assay and nitric oxide scavenging assay. The trypan blue exclusion method was used to study the antitumor activity of the polysaccharide on Daltons Lymphoma Ascites (DLA) cells. The results indicated that the polysaccharide from Ulva fasciata has potent antioxidant and antitumor activity.